2019
DOI: 10.1111/jphd.12339
|View full text |Cite
|
Sign up to set email alerts
|

Who provides open‐ended comments? Assessing item nonresponse bias in Medicaid surveys of members and dentists

Abstract: Objectives This aim of this study was to examine factors associated with survey item nonresponse to open‐ended items in mailed surveys. Methods Data sources include two surveys conducted in Iowa in 2016 – one to a random sample of Medicaid dental program members and one to private practice dentists. Item nonresponse bias for open‐ended comments was examined by comparing differences between commenters and noncommenters. Bivariate and logistic regression analyses examined differences based on demographic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Among dentists, respondents were significantly more likely to be older and in solo practice compared to nonrespondents . An examination of item nonresponse bias among members revealed that respondents who provided open‐ended comments were more likely to be Black, older, unemployed, have had a recent dental visit, and to have rated their dental plan poorly compared to those who did not provide comment (Reynolds JC, McKernan SC, Sukalski MC, unpublished data,). Among dentists, those who provided open‐ended comments were more likely to participate in the DWP than those who did not provide comment.…”
Section: Resultsmentioning
confidence: 99%
“…Among dentists, respondents were significantly more likely to be older and in solo practice compared to nonrespondents . An examination of item nonresponse bias among members revealed that respondents who provided open‐ended comments were more likely to be Black, older, unemployed, have had a recent dental visit, and to have rated their dental plan poorly compared to those who did not provide comment (Reynolds JC, McKernan SC, Sukalski MC, unpublished data,). Among dentists, those who provided open‐ended comments were more likely to participate in the DWP than those who did not provide comment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the non-response on these questions may be systematically biased, as differences in response rates among individuals with different characteristics (e.g. politically interested versus non-interested) tend to be higher on cognitively burdensome questions (Holland & Christian, 2009;Reynolds et al, 2020).…”
Section: Closed-ended Versus Open-ended Questionsmentioning
confidence: 99%